JUSTIFICATION OF THE COMPOSITION AND TECHNOLOGY OF THE GEL FOR THE TREATMENT OF WOUNDS AND BURNS WITH SAGE MEDICINAL EXTRACT - РОЇК, О. М.; НІКІТІНА, О. О. (Technologies and Engineering, 2023)
The purpose is to develop an optimal composition and technology for the production of a gel-based drug for the treatment of wounds and burns with Sage medicinal extract. Establish physico-chemical and technological characteristics of the properties of the developed agent. Methodology. Theoretical and empirical methods used in the work are the study of literature on the chosen topic; methods of comparative analysis, systematic approach, experimental research, synthesis, statistical methods for collecting and processing information. Results. The Ukrainian market of drugs for the treatment of wounds and burns was analyzed and it was found that this group of drugs is represented by 105 drugs of various forms of release. In Ukraine, the largest share is occupied by soft-release drugs, and the development of such a dosage form that would meet the requirements for an ideal coating is an actual direction in modern drug technology. The substantiation of the introduction of sage medicinal extract has been carried out. One of the most promising forms for the treatment of wounds and burns are gels, which are soft drugs, which are intended for topical application. According to the results of the studies, phenylethyl alcohol at a concentration of 0.4% was chosen as the most acceptable preservative in the composition of the developed gel, which is due to the manifestation of its high antimicrobial activity in this pharmaceutical composition, physiological safety, economy, and the possibility of its use as a flavoring agent. The manufacturing process of the developed gel for the treatment of wounds and burns consists of the stage of auxiliary work; stages of drug manufacturing; stages of packaging, labeling and shipment to the warehouse of finished products. Scientific novelty. Based on the studies, the optimal composition of the gel for wounds and burns was substantiated and its composition was calculated as follows: Extract from sage leaves – 10%, tea tree oil1,0%, lidocaine hydrochloride – 2%, Chlorhexidine digluconate – 2%, carbomer Carbopol® «Ultrez 21» – 1%; trometamol – up to pH 6.0, propylene glycol – 5%, phenylethyl alcohol – 0.4% and purified water – up to 100.0. A technological scheme of production has been developed and a stage-by-stage quality control of the developed gel has been carried out. According to the results of microbiological studies, the expediency and effectiveness of the introduction of the antimicrobial preservative phenylethyl alcohol at a concentration of 0.4% was confirmed. On the basis of the data obtained, the conditions for storing the gel from wounds and burns are proposed – at a temperature of 2–8 °C in tubes of 30.0 g in a place protected from light, the shelf life is 2 years. Practical significance. The composition of the gel for the treatment of wounds and burns is calculated and can be used for industrial production and it can complement the existing range of drugs on this issue.